The Impact Of Digital Transformation On Commercial Banks Performance- Algerian Banks Employees As A Sample- - Haddad Meroua; Boufoula Nabila (جامعة الوادي University of Eloued, 2024)
The study aims to measure the connection between digital transformation and banks’ performance in the first place, then to evaluate the impact of digital transformation and its dimensions: digital infrastructure, digital offices, and digital services on banks’ performance in Algeria, on the grounds that digital transformation has become a sine qua non for all organizations generally and financial institutions, such as banks specifically, for their activities and performances in a world depending on technology and digital nowadays. Relying on quantitative study targets Algerian bank employees, to assess the impact, a questionnaire was distributed to them, 51 forms were collected, and analyzed using the SPSS version 26 programs, resulting in the findings that digital transformation has a positive effect on bank performance.
Keywords: digital transformation; commercial banks; performance